IMPLEMENTASI KEBIJAKAN SIMTANAS DI KANTOR PERTANAHAN KABUPATEN BONE - Saguni, Dewi Sulfa; Kurniadi, Hanif; Djabbari, Muhammad Hidayat; Widyawati, Widyawati (Politeknik STIA LAN Makassar, 2024)
Every organization, including government agencies, aims to provide optimal services and compete effectively. This research aims to investigate, identify, and analyze the implementation of the SIMTANAS policy in Bone Regency using a descriptive method and a qualitative approach. Data was collected through observation, unstructured interviews, and a review of relevant literature and documents. Informants included the Head of the Bone Regency Land Office, SIMTANAS implementation staff, the project coordinator for land digitalization, and Bone Regency residents using SIMTANAS services, such as farmer groups and local communities involved in land use. Data analysis was conducted using the Interactive Model Analysis technique. The results indicate that the implementation of SIMTANAS in Bone Regency is influenced by six main factors: policy standards, resources, inter-organizational communication, implementer characteristics, social, economic, and political conditions, and the disposition of the implementers.